2 Vibration Profiles of Commercial Straight-Deck Trailers Transporting Market-Weight Pigs During Summer. (21st September 2022) - Alambarrio, Daniela A; Davis, Benjamin; Morris, Benjamin; Gonzalez, John M; Turner, Kari K
Abstract: The objective was to collect and quantify three-axis acceleration data from locations within commercial transport trailers shipping market weight pigs during summer. Two trucks and straight-deck trailers, owned and operated by a single producer, were observed during two loads per day for five consecutive days. Three-axis accelerometers were placed under top and bottom deck floors in the center of the fore, center, and aft compartments. Z-axis and combined x- and y-axis data were processed to generate root-mean-square (RMS) values and vibration dose values (VDV) during loading, trailer movement, and unloading. At all periods of the trip and both sets of axis data, there were no Deck × Area interactions (P > 0.11) for RMS and VDV values. During loading and movement, the bottom deck had greater z-axis RMS and VDV values than the top deck (P < 0.01), but there was no difference (P = 0.07) during unloading. There were no Area effects for z-axis RMS and VDV values during all time periods (P > 0.06). During all periods, the top deck had greater x, y-axis RMS values than the bottom deck (P < 0.02). During loading and movement, the bottom deck had greater x, y-axis VDV values than the top deck (P < 0.03), but there was no difference (P = 0.52) during unloading. There were no Area effects for x, y-axis RMS and VDV values during all time periods (P > 0.07). Individual trip RMS and VDV values were compared with exposure action values (EAV; injury possible) and exposure limit values (ELV; injury likely). At all parts of the trip, trailer RMS and VDV violated between 51% and 99% EAV and ELV thresholds. These data indicate top and bottom decks vibrate differently and pigs experience vibrations that may contribute to fatigued pig syndrome or the non-ambulatory condition.